Improving Student Asking Activity by Using Learning Start with a Question (LSQ) Learning Method - Delasari, Patimah; Nugraha, Fajar; Zahrah, Riza Fatimah (Universitas Sebelas Maret, 2021)
This study aims to meet whether the Learning Start With A Question (LSQ) learning method can be used to improve the results of questioning activeness in grade IV SD Negeri Pereng. This research method is Classroom Action Research (PTK), using the model of Kesmis and Mc. Taggart. The subjects in this study were the fourth grade students of SD Negeri Pereng, Tasikmalaya Regency, totaling 17 students. Data collection techniques in the form of student observation sheets, tests to determine the ability to ask questions and administrative learning documents. The results showed that the use of the Learning Start With A Question (LSQ) learning method in social studies learning could increase the activeness of the fourth grade students of SD Negeri Pereng, Tasikmalaya Regency. Based on the test results obtained by students at the end of each cycle, it showed an increase in student questioning activity. The average completeness in the first cycle was 47.35, and the average completeness in the second cycle was 67.64, while the average of the third cycle was 78.82. The results show that the quality of the learning process, especially in questioning activeness, has increased.